Contractor's plant: whether to buy or to lease? - Muller, Marius M. (University of the Free State, 1997)
This article comments on the concepts of buying versus leasing in terms of decision-making theory regarding the procurement of contractor's plant. It was found that leasing offered the better option in the worked example presented herein, but that every plant buying or lease decision would have to be made individually on proven calculation and on merit. In hierdie ortikel word die bestoonde opsies behondel woorvoor die boukontrokteur te stoon kom wonneer hy toerusting oonskof. Die vroog is: moet hy huur of koop. Uit die voorbeeld wot hier oongehool word blyk dit dot huur 'n beter opsie bied. Dit is egter ook boie duidelik dot elke gevol meriete het en dus individueel bekyk moet word. Kostes moet teen mekoor opgeweeg word. verol met die kontrokteur se doelwit voor oe.
Keywords: Plant; Purchasing; Leasing; Hiring